Gender-related traits as predictors of alcohol use in male German and Spanish university students - Zimmermann, Friederike; Sieverding, Monika; Müller, Stephanie M. (Sex roles, 2011)
This study examined instrumental (masculine stereotyped) and expressive (feminine stereotyped) personality traits and alcohol use among men from Germany and Spain. Participants were 161 male university students (76 German, Mage = 23 years; 77 Spanish, Mage = 22 years), who completed either a daytime or a nighttime drinking questionnaire, each including a Short Form of the Bem Sex Role Inventory. Poisson regression analyses with latent predictors were conducted. The trait factors and their interactions with nationality predicted daytime and nighttime alcohol use. The results add support to the assumption that alcohol use is associated with the construction of masculinity and that internalization of traditionally female attributes protects against health-risk behaviors such as alcohol consumption.
Published online: 23 November 2010
Gesehen am 19.01.2023